Sistim Pakar Konseling Mata Pelajaran Pilihan UNBK Menggunakan Metode Forward Chaining - Laidawati, Desi; Yunus, Yuhandri (Jurnal Sistim Informasi dan Teknologi, 2019)
The choice of computer-based national exams is a choice of a student that must be adjusted to his interests and talents, so in this case the selection of majors is very important for the future of a student who will continue his studies to college. But in reality the decisions taken in choosing majors often cause problems, because the Majors taken only follow the choice of friends or on the basis of coercion from parents. Causing the large number of students who feel out of line with expectations or abilities and want to change majors. For this reason, an expert system has been made that can make it easy for students to consult early to determine elective subjects for computer-based national examinations. The method used in making this expert system is the Forward Chaining method to determine conclusions. The process of this application is to receive input in the form of types of problems experienced by students. The result of the application is that it can provide early instructions for subjects that match the talents and interests of students. With the application of the forward chaining method that is applied to the system that is governed by the rule type problem. From the accuracy of 89.29%, the system can be said to be good enough to be implemented